Providing a model of religious tourism based on the art of ta\'ziyeh (case study: Kashan city) - Mohammad reza Heydari; Mehrdad Sadeghi; Ali Rashidpoor (تحقیقات کاربردی علوم جغرافیایی)
The purpose of this study is to present a model of religious tourism based on the art of taziyeh in Kashan based on structural equation modeling, based on a mixed exploratory approach. In the qualitative part, the phenomenological method was used and in the quantitative part, the descriptive method, correlation based on structural equations was used. The statistical population of this research in the qualitative part included professors and experts in tourism and condolence in Kashan, which was obtained after 15 saturated interviews. In order to evaluate the validity of qualitative data, structural, external, descriptive and interpretive validity were used and in order to evaluate the reliability, the three approaches of Rao and Perry (2003) were used. The results of qualitative research were extracted from 11 economic, strategic, development, research, organizational, technical, content, environmental and advertising dimensions. After examining the extraction of components, the quantitative part of the research was examined. Factor and content validity were used to evaluate the validity. The reliability of the questionnaire was used from Cronbach's alpha, which had the necessary reliability. Available was selected. The data obtained from the questionnaires were analyzed at two levels of descriptive and inferential statistics, including structural equations, through SPSS 22, LISREL 18.9 and Warp PLS 5 software. Findings showed that the most impact was economic dimension (impact factor 0.86) followed by cultural dimension with (0.79) and strategic dimension with (0.78).